Gut microbiome signature in response to neoadjuvant chemoradiotherapy in patients with rectal cancer - Duan, Tingmei; Ren, Zhengting; Jiang, Haili; Ding, Yan; Wang, Hongyan; Wang, Fan (Frontiers in Microbiology, 2025)
BackgroundRectal cancer remains a leading cause of cancer-associated mortality, especially in advanced cases with limited treatment options. Emerging evidence suggests that the gut microbiome may influence the therapeutic efficacy of neoadjuvant chemoradiotherapy (CRT).ObjectiveThis study aimed to explore the dynamic changes in gut microbiome composition and metabolic pathways in rectal cancer patients undergoing CRT.MethodsPaired fecal samples were collected from rectal cancer patients pre- and post-CRT. 16S rRNA amplicon sequencing and proteomics analysis were conducted to investigate microbial and metabolic alterations.ResultsSignificant shifts in the microbiome were observed, with Fusobacterium, Subdoligranulum, Prevotella, Alloprevotella, and Bacteroides being enriched pre-CRT, while Streptococcus, Megamonas, Megasphaera, Escherichia-Shigella, and Olsenella became dominant post-CRT. Metabolic analysis revealed upregulated carbohydrate metabolism and downregulated lipid and energy metabolism.ConclusionThese findings identify potential microbial biomarkers and metabolic pathways associated with CRT response, offering insights into personalized treatment strategies.